Characterization of Smallholder Beef Cattle Production System in Central Vietnam –Revealing Performance, Trends, Constraints, and Future Development - D. V. Dung; H. Roubík; L. D. Ngoan; L. D. Phung; N. X. Ba (Faculty of Animal Science, Bogor Agricultural University, 2019)
The objective of this study is to evaluate the characteristics of smallholder beef cattle production in Central Vietnam. A total of 360 households were interviewed by using semi-structured questionnaire; a total of 606 beef cows were investigated for evaluating calving interval (CI). Thirty-two fattening cattle were monitored for the estimation of diet structure. Results showed that the cattle herd size was 4.32-4.45 cattle/household. In North Central (NC), 55% of surveyed farmers kept local cattle, 45% kept crossbreeds, and none of surveyed farmers keeping exotic breeds. In South Central (SC), 63% of surveyed farmers kept cross cattle, 32% kept local cattle, and 5% kept exotic breeds. In the breeding method, 70% of surveyed farmers used artificial insemination (AI), 20% used natural mating (NM), and only 10% used both AI and NM in SC, whereas in NC 40% of farmers used AI, 40% used NM, and 20% used both AI and NM. The variety of feedstuffs fed to cattle including roughages and concentrate. The concentrate in the diet for fattening cattle was 25%-35% and protein level was 11%-13%, and the average daily gain of cattle was 0.51-0.63 kg/day. The CI of cows was 12-13 months in SC, whereas in NC it was 13-14 months. There were numerous constraints to cattle production in surveyed households including diseases, lack of good quality feed sources, breeds, knowledge, and lack of capital. In conclusion, cattle production in Central Vietnam is small scale and still largely extensive. There are constraints that must be solved to improve livestock systems in the near future, especially when shifting towards semi-intensive and/or intensive cattle production systems.